Deep Cerebral Perforators: Anatomical Distribution and Clinical Symptoms. Issue 10 (October 2021) - Vogels, Valerie; Dammers, Ruben; van Bilsen, Martine; Volovici, Victor
Abstract : The anatomic distribution of the deep cerebral perforators is considered either a given or subject to enormous variability. Most published overviews on this topic only report findings from a limited number of anatomic dissections, and no attempt has been made to date to provide a comprehensive overview of all published data. A comprehensive literature search was performed on MEDLINE, Embase, and Google Scholar with the help of an information specialist. Three types of studies were included: (1) articles that described the anatomy and distribution territories of perforator groups arising from the arteries of the circle of Willis; (2) studies that evaluated the anatomy of the deep cerebral perforators using imaging techniques; and (3) studies that evaluated either microsurgically or radiologically confirmed perforator occlusion and reported the (magnetic resonance imaging–confirmed) distribution territory of the infarction together with a description of the clinical symptoms associated as a result of the infarction. A total of 2715 articles were screened and 53 were included. Of these, 40 dealt with the anatomic and imaging anatomy of perforator groups (37 reported results of dissections and 3 results of imaging studies), with a total of 2421 hemispheres investigated. Another 13 articles with 680 patients were included that evaluated perforator infarction territories. The deep cerebral perforator distribution shows large variability with poor concordance rates among reported studies, with the exception of the posterior communicating and anterior choroidal artery perforators. Despite the assumption that cerebral perforator anatomy is a given, studies show large variability in the anatomic distribution of various perforator groups. Perforator anatomy and relationships between perforator groups, as well as potential collateral circulation in these territories should be prioritized as a research topic in cerebrovascular disease in the near future. Abstract : Supplemental Digital Content is available in the text.